2020
DOI: 10.1002/slct.202002891
|View full text |Cite
|
Sign up to set email alerts
|

Alkanolammonium Protic Ionic Liquids for Low Temperature 68Ga‐Radiolabeling of DOTA‐Functionalized Compounds

Abstract: Nowadays, the radiolabeling of small biomolecules with isotope 68Ga is one of the important directions in the field of Positron‐Emission Tomography (PET). The right choice of buffer for reaction helps to achieve optimal conditions for higher yields. Earlier, we found that protic ionic liquids based on tris(2‐hydroxyethyl)ammonium and tris(hydroxymethyl)methyl ammonium salts are suitable buffers for the chelation of the 68Ga to the PSMA‐HBED‐CC (a peptide with an acyclic chelator). Herein we describe the labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The 68 Ga‐DOTA complex, as a rule, is easily formed at 95 °C and the addition of ethanol as a co‐solvent with high radiochemical conversion (RCC) [22] . Earlier, our group showed that 68 Ga complexes with BCAs and clinically significant peptides could be obtained in the medium of hydroxyalkylammonium salts at 37 °C and using acetone as a co‐solvent [9b] …”
Section: Resultsmentioning
confidence: 99%
“…The 68 Ga‐DOTA complex, as a rule, is easily formed at 95 °C and the addition of ethanol as a co‐solvent with high radiochemical conversion (RCC) [22] . Earlier, our group showed that 68 Ga complexes with BCAs and clinically significant peptides could be obtained in the medium of hydroxyalkylammonium salts at 37 °C and using acetone as a co‐solvent [9b] …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is common knowledge that DOTA makes stable complexes with many isotopes in addition to gallium-68 and provides stability of bioconjugates in vitro and in vivo. The full evaluation was carried out with using of high-temperature (HT) and low-temperature (LT) radiolabeling protocols [ 23 , 25 , 26 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, a similar result was found for salts 5 and 6 . In our previous works [ 23 , 24 , 25 , 26 , 36 ], ILs containing 2-methylphenoxyacetate and 4-chloro-2-methylphenoxyacetate anions as buffering agents provide almost quantitative RCCs for the reaction of 68 Ga radioisotope with the DOTA chelator. BEA salts 4 , 9 and 10 showed average RCCs in the 40–65% range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint research with Granov Russian Scientific Center of Radiology and Surgical Technologies [ 95 , 96 ] have shown that the synthesized hydroxyalkylammonium carboxylates are promising buffering agents for the preparation of gallium-68 complexes with chelators and peptides. The 68 Ga complexes with a series of clinically important peptides are radiopharmaceuticals important in the nuclear medicine for the diagnostics of various neoplasms.…”
Section: Protatranesmentioning
confidence: 99%